Evaluating the Intention and Behaviour of Private Sector Participation in Healthcare Service Delivery via Public-Private Partnership: Evidence from China. (17th January 2020) - Yang, Jie; Song, Lingchuan; Yao, Xiaoyi; Cheng, Qian; Cheng, Zichao; Xu, Ke
Abstract : Private sector participation in the healthcare market via public-private partnership (PPP) could be considered an available approach to narrow down the medical resource gap and improve the operational efficiency of healthcare facilities. Accordingly, this study aims to examine the influence and relative importance among critical factors for the intention and behaviour of the private sector towards participation in Chinese healthcare market (CHM) via PPP. We defined five hypotheses from previous literature and built a theoretical model based on modified theory of planned behaviour. Then, covariance-based structural equation modelling was applied to analyse the questionnaires provided by 248 respondents from construction companies, real estate developers, pharmaceutical companies, private hospitals, asset management companies, and medical industry property investment companies in China. Results indicated that attitude towards behaviour ( β = 0.466, P < 0.001 ), subjective norm ( β = 0.167, P < 0.05 ), perceived behavioural control ( β = 0.231, P < 0.01 ), and facilitating conditions ( β = 0.305, P < 0.001 ) are positively significant to behavioural intention; behavioural intention also shows a strong linkage with behaviour ( β = 0.931, P < 0.001 ). Findings provide reference for governments and public authorities to exert additional efforts in implementing appropriate measures that will stimulate the private sector's motivation to participate in CHM via PPP.